Geographic Information System of Dengue Hemorrhagic Fever Area Mapping in the City Of Samarinda - Tarsius Aloysius Pedor; Syafei Karim; F.V Astrolabe Sian Prasetya (TEPIAN, 2021)
Dengue Hemorrhagic Fever (DHF) is still one of the main public health problems in Indonesia. This disease can threaten public health, efforts to prevent its spread need to be done. As the first step for prevention, it is necessary to do the mapping. Environmental factors have a major influence on the increase and transmission of mosquito-borne diseases such as DHF. The most influential factors include the physical environment consisting of rainfall, air humidity, and population density. The city of Samarinda itself has not maximized the DHF control program, because the government is less effective in mapping the DHF-vulnerable areas based on indicators of increasing cases over the last few years using spatial maps. Mapping the DHF area with the spatial method can maximize the implementation of the DHF control program, the implementation of the fogging program, and other DHF control programs. So to get this information, a geographical information system (GIS) is needed or commonly known as a geographic information system (GIS). This web-based geographic information system application for mapping dengue areas can display detailed information such as the address of the Public Health Center that provides information on the number of cases that occur in each sub-district and a polygon map showing which sub-district has the most cases.